Cardiac magnetic resonance elastography: toward the diagnosis of abnormal myocardial relaxation - Elgeti, Thomas; Beling, Mark; Hamm, Bernd; Braun, Jürgen; Sack, Ingolf (Investigative radiology, 2010)
To assess the potential of cardiac magnetic resonance elastography (MRE) for elasticity-based detection of abnormal left ventricular (LV) relaxation. Cardiac MRE was performed in 3 groups: young volunteers (n = 11; mean age, 31.7 years), older volunteers (n = 5; mean age, 54.8 years), and a group with relaxation abnormalities (n = 11; mean age, 58 years) identified by transthoracic echocardiography. Cine MR imaging served to measure LV volumes and global LV systolic function. Wave-amplitude-sensitive electrocardiograph-gated steady-state MRE was performed using an extended piston driver attached to the anterior chest wall. Phase contrast shear wave images were acquired in all 3 Cartesian components and combined to generate amplitude maps. This was done using the time-gradient operator for linear high-pass filtering and phase unwrapping followed by temporal Fourier transformation for extracting externally induced 24.13-Hz shear oscillations from intrinsic motion and blood flow. Amplitudes were evaluated in the left ventricle and normalized by wave amplitudes outside the heart, adjacent to the right ventricle. One patient and 1 young volunteer had to be excluded from final analysis because of considerable body movement during the acquisition of the MRE scans. Mean wave amplitudes in the remaining subjects were 0.22 ± 0.05 mm in young volunteers, 0.23 ± 0.09 in older volunteers, and 0.14 ± 0.03 mm in patients. The mean ratio of amplitudes inside the ventricle to the anterior chest wall was 0.62 ± 0.15 for young volunteers, 0.50 ± 0.09 for older volunteers, and 0.33 ± 0.08 for patients. MRE identifies significantly reduced LV shear wave amplitudes in patients with mild relaxation abnormality. Thus, cardiac MRE provides a promising modality for an elasticity-based diagnosis of dysfunctional myocardial relaxation.